High Degree of Parasitemia Induces Placental Hypoxia and Low Birth Weight - Nurfianti Indriana; Zainabur Rahmah; Alvi Milliana (Faculty of Medicine, University of Jember, 2022)
Placental malaria causes low fetal weight associated with infiltration of monocytes and parasites in the placenta resulting in placental hypoxia. Hypoxia is characterized by HIF expression. HIF-1Î± expression responds early to the occurrence of hypoxia (<24 hours) and HIF-2Î± promotes chronic hypoxia (>24 hours). There were two groups in this study, namely the control group (10 pregnant mice without Plasmodium berghei infection) and the treatment group (10 pregnant mice infected with Plasmodium berghei). Pregnant mice were operated on on the 18th day after mating. The degree of parasitemia was measured by Giemsa staining. Expression of HIF-1Î± and HIF-2Î± in placental tissue was measured by immunohistochemistry. Results by paired t test, HIF-1Î± expression in the placental tissue in the treatment group was higher than the control group (p=0.02), HIF-2Î± expression in the placental tissue was higher in the treatment group than in the control group (0, 01) the fetal weight in the treatment group was lower than in the control group (p=0.01). By using SEM analysis, the degree of parasitemia caused high expression of HIF-1Î± in placental tissue (tcount = 4.625, ttable = 1.96). High expression of HIF-2Î± in placental tissue (tcount = 2.672 ttable = 1.96). The degree of parasitemia causes low fetal weight (tcount = 27.764 ttable = 1.96). The results also showed that HIF-1 caused low birth weight (tcount = 2.376 ttable=1.96) also HIF-2Î± caused low fetal weight (tcount = 4.267 â‰¥ 1.96). Conclusions the degree of parasitemia causes high expression of HIF-1Î± and HIF-2Î± in placental tissue and low birth fetuses. Expression of HIF-1Î± and HIF-2 also causes low birth weight. Keywords: malaria in pregnancy, degree of parasitemia, HIF-1Î± , HIF-2Î± , birth weight